Authentic cell-specific and developmentally regulated expression of pro- opiomelanocortin genomic fragments in hypothalamic and hindbrain neurons of transgenic mice - Young, J.I. (1998)
The pro-opiomelanocortin (POMC) gene is expressed in a subset of hypothalamic and hindbrain neurons and in pituitary melanotrophs and corticotrophs. POMC neurons release the potent opioid β-endorphin and several active melanocortins that control homeostasis and feeding behavior. POMC gene expression in the CNS is believed to be controlled by distinct cis- acting regulatory sequences. To analyze the transcriptional regulation of POMC in neuronal and endocrine cells, we produced transgenic mice carrying POMC27*, a transgene containing the entire 6 kb of the POMC transcriptional unit together with 13 kb of 5' flanking regions and 8 kb of 3' flanking regions: POMC27* was tagged with a heterologous 30 bp oligonucleotide in the third exon. In situ hybridization studies showed an accurate cell-specific pattern of expression of POMC27* in the arcuate nucleus and the pituitary. Hypothalamic mRNA-positive neurons colocalized entirely with β-endorphin immunoreactivity. No ectopic transgenic expression was detected in the brain. Deletional analyses demonstrated that neuron-specific expression of POMC transgenes required distal 5' sequences localized upstream of the pituitary- responsive proximal cis-acting elements that were identified previously. POMC27* exhibited a spatial and temporal pattern of expression throughout development that exactly paralleled endogenous POMC. RNase protection assays revealed that POMC27* expression mimicked that of POMC in different areas of the CNS and most peripheral organs with no detectable ectopic expression. Hormonal regulation of POMC27* and POMC was identical in the hypothalamus and pituitary. These results show that distal 5' sequences of the POMC gene located between -13 and -2 kb target expression into the CNS of transgenic mice in a precise neuron-specific, developmentally and hormonally regulated manner.